Determinants of Childbearing Age Couples Perform Early Detection of Cervical Cancer Through IVA Method (Visual Inspection of Acetic Acid) in Sigi Regency - Badariati; Ratna Devi; Mursyidah Khairiyah; Parmin (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Cervical cancer is a malignant disease that is quite often heard among the public. Cervical cancer or commonly referred to as cervical cancer often occurs in women. Cervical cancer can occur due to a poor lifestyle and environment, such as having free sex, changing partners and a lack of personal hygiene. Objective: This study aims to determine the determinants of early detection of cervical cancer in couples of childbearing age (PUS) in Sigi Regency. Method: This study used a cross sectional research design. Result: There was a significant relationship between knowledge, attitude and behavior of early detection of cervical cancer in Sigi Regency. There was no significant relationship between education, employment and support of health workers and early detection behavior of cervical cancer in Sigi Regency. Conclusion: This study concluded that there is a significant relationship between knowledge, attitudes and behaviors for early detection of cervical cancer in Sigi Regency. And there was no significant relationship between education, employment and support of health workers and early detection behavior of cervical cancer in Sigi Regency.